Passive muscle tension increases in proportion to intramuscular fluid volume - Sleboda, D. A.; Wold, E. S.; Roberts, T. J. (The Journal of Experimental Biology, 2019)
During extended bouts of exercise, muscle can increase in volume by as much as 20% as vascular fluid moves into the tissue. Recent findings suggest that the fluid content of muscle can influence the mechanics of force production; however, the extent to which natural volume fluctuations should be expected to influence muscle mechanics in vivo remains unclear. Here, using osmotic perturbations of bullfrog muscle, we explored the impacts of physiologically relevant volume fluctuations on a fundamental property of muscle: passive force production. We found that passive force and fluid volume were correlated over a 20% increase in muscle volume, with small changes in volume having significant effects on force (e.g. a 5% volume increase results in a >10% passive force increase). A simple physical model of muscle morphology reproduces these effects. These findings suggest that physiologically relevant fluid fluxes could alter passive muscle mechanics in vivo and affect organismal performance.